Academic Supervision and Reflective Literacy-based Teacher Performance Management in Elementary Schools - Winarti, Winarti; Salamun, Salamun; Wahyudi, Apri (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to explore the potential effects of academic supervision and reflective literacy on teacher effectiveness. Using a qualitative approach and a case study design, the study was conducted in a public elementary school in Tulang Bawang Regency, Indonesia. Data were collected through semi-structured interviews with 14 participants (1 principal, 2 supervisors, and 11 classroom teachers). In addition, records from performance reviews, supervision reports, and teacher reflection journals were examined, and six classroom learning sessions were directly observed. The results demonstrate that typical supervision, which focuses solely on administrative tasks, is insufficient to improve instructors' instructional competency. However, teachers who actively engaged in reflective literacy practices such as updating lesson plans, interacting with colleagues and journaling independently showed significant performance improvements. This group of reflective teachers achieved an average performance score of 85/100, compared to the mere 70/100 for non-reflective teachers. They may also change their teaching methods three or four times a semester since they become more adaptable. Principal leadership, which sees supervision as a coaching process, is one crucial component of strength. The study's conclusions indicate that the integration of reflective literacy transforms academic supervision into a teacher-centered professional learning process.